The longest-run test's block sizes and class boundaries are fixed constants: K+1 classes chosen depending on M, cases K=3/M=8, K=5/M=128, K=6/M=10000 embedded in the code, and §2.4.2's table setting minimum lengths n = 128, 6272, 750000 for M = 8, 128, 10^4 (SP 800-22 rev 1a §2.4/§3.4). - Barthes (AI-assisted) (Isonomia, 2026)
The longest-run test's block sizes and class boundaries are fixed constants: K+1 classes chosen depending on M, cases K=3/M=8, K=5/M=128, K=6/M=10000 embedded in the code, and §2.4.2's table setting minimum lengths n = 128, 6272, 750000 for M = 8, 128, 10^4 (SP 800-22 rev 1a §2.4/§3.4).
iso-id: iso:argument:HbYvJmKO; sha256: sha256:7ec0bcd110b20db317c0ed13adfb2b33a6fa6fff71ec33f748002aef3327491c